[Magnetic resonance spectroscopy for inflammatory brain diseases]. - Papanagiotou, P; Grunwald, I; Farmakis, G; Hartmann, K; Politi, M; Roth, C; Reith, W (2008)
Magnetic resonance spectroscopy (MRS) is a non-invasive method for investigation of cerebral metabolite concentrations in various pathologic conditions. The clinical use of MRS for intracranial disorders is well established. In this review the characteristic MRS findings for the most important inflammatory brain diseases will be discussed.